2008
DOI: 10.1111/j.1600-9657.2008.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal healing of replanted dog teeth stored in milk and egg albumen

Abstract: The type of storage medium used to store avulsed teeth prior to replantation has been shown to be a decisive factor in periodontal ligament (PDL) healing. The aim of the present study was to investigate the effect of storage medium on periodontal healing. Thirty teeth from three dogs were endodontically treated to prevent subsequent inflammatory root resorption. The teeth were atraumatically extracted and randomly stored in milk or egg albumen for 3, 6 and 10 h at 4 degrees C. All teeth were splinted for 1 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 17 publications
(28 reference statements)
5
46
0
2
Order By: Relevance
“…They were promising concerning the organization of collagen fibres and the number of viable cells. Some suggest that they can be perfect media for storing avulsed teeth but they need additional studies [4,6,[18][19][20][21]. Some considered milk as a gold standard for transporting avulsed teeth.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…They were promising concerning the organization of collagen fibres and the number of viable cells. Some suggest that they can be perfect media for storing avulsed teeth but they need additional studies [4,6,[18][19][20][21]. Some considered milk as a gold standard for transporting avulsed teeth.…”
Section: Methodsmentioning
confidence: 99%
“…However, other studies demonstrated that egg white reported higher viable PDL cells than milk after half hour storage time [25,26]. On the same context Khademi., et al found that teeth stored in egg white for 6 to 10h had a better incidence of repair and lower surface resorption than those stored in milk [20]. According to the International Association of Dental Traumatology and the American Academy of Pediatric Dentistry milk is considered as the second or third best transportation media for avulsed teeth include after Viaspan and/or HBSS [23,27].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The osmolality of the egg white is between 251 and 298 mOsm/kg [24]. de Sousa et al have microscopically analyzed, the human PDL attached to the extracted tooth after 1 hr of extra alveolar time, compared to milk, egg white, and artificial saliva.…”
Section: Egg Whitementioning
confidence: 99%